G238 "safety huddles": multidisciplinary views regarding the purpose and effectiveness of a novel paediatric situational awareness tool. (27th April 2015) - Adams, J; Conn, R; Gohil, R
Abstract : Aim: Following an audit in 2012, which identified variability in the recognition and escalation of deteriorating patients, Safety Huddles were introduced, utilising a Childrens' Early Warning Score (CEWS), to enhance situation awareness. Huddles are scheduled, regular multi-professional meetings, no longer than ten minutes, held in the clinical environment alongside an interactive electronic patient board. The sickest and most at risk patients (CEWs > 2) are identified, prompting immediate and appropriate escalation. Four additional risk factors (family concerns, high risk therapies, clinicians' gut feeling and communication concerns) further identify patients as 'watchers'. Huddles provide: - Optimum safety through elimination of avoidable harm - Greater empowerment and accountability of all staff through shared decision making Our aim was to evaluate the attitudes and understanding of front-line staff regarding the purpose and effectiveness of Huddles, 18 months on. Methods: A voluntary, anonymous online survey was disseminated to staff across 3 clinical areas (2 wards, 1 outpatients). Ethical approval was not required. Results: 41 responses were returned. Respondents included 2 consultants, 4 registrars, 24 nurses, 1 nursing student, 1 healthcare assistant, 2 pharmacists and 5 interpreters. The majority rated their understanding regarding the purpose of the Huddle as "good" (51%) or "excellent" (41%). 88% described the Huddle as an "important aspect" of their work, 98% no longer requiring reminders to attend. Subjectively, the Huddle led to improvements in: Team Communication (95%), Patient/carer involvement (63%), Staff support (80%), identification of deteriorating patients (93%) and timely escalation (90%). 83% felt better informed about patients not specifically allocated to their care. 50% felt Huddles should occur with increased frequency. Crucially, 93% felt enabled to have their concerns heard. Problems identified included punctuality of start times and occasional non-attendance of doctors, which subjectively lessened the value of the Huddle. Conclusion: Huddles are regarded as useful by the vast majority of staff and are an inclusive, empowering, non-hierarchical method of information sharing regarding patient safety. Our findings have been shared with all staff and suggested modifications are being considered. Huddles are now being introduced across UK 12 sites as part of the SAFE collaborative of RCPCH.